Perceptions of climate and environmental change in Northcentral Kansas - Wilson, Iris E. (Kansas State University, 2011)
Global and regional climates have changed significantly in recent decades. One of the sectors most affected by a changing climate is agriculture. While the scientific consensus is clear that climate has changed, a declining number of Americans believe in the seriousness of “global warming”. Bridging this knowledge gap will require a more in depth understanding of public perceptions of climate change. The research reported here addressed public perceptions of climate and environmental change in north central Kansas and found that farmers are aware that climate has changed over their lifetimes. Local residents were found to be aware on ongoing environmental changes and adopting changes in land management practices that balance improving environmental conditions with the need to make a profit. More information is needed on what information sources and presentation styles would work best for the communication of updated information, both for communicating with farmers and with educators.
Keywords: Climate change; Climate perceptions; Kansas; Environmental perceptions; Agriculture, General (0473); Climate Change (0404); Environmental management (0474); Geography (0366)